Mitochondrial Dysfunction: An Emerging Link in the Pathophysiology of Cardiorenal Syndrome - Shi, Shuqing; Zhang, Bingxuan; Li, Yumeng; Xu, Xia; Lv, Jiayu; Jia, Qiulei; Chai, Ruoning; Xue, Wenjing; Li, Yuan; Wang, Yajiao; Wu, Huaqin; Song, Qingqiao; et al. (Frontiers in Cardiovascular Medicine, 2022)
The crosstalk between the heart and kidney is carried out through various bidirectional pathways. Cardiorenal syndrome (CRS) is a pathological condition in which acute or chronic dysfunction in the heart or kidneys induces acute or chronic dysfunction of the other organ. Complex hemodynamic factors and biochemical and hormonal pathways contribute to the development of CRS. In addition to playing a critical role in generating metabolic energy in eukaryotic cells and serving as signaling hubs during several vital processes, mitochondria rapidly sense and respond to a wide range of stress stimuli in the external environment. Impaired adaptive responses ultimately lead to mitochondrial dysfunction, inducing cell death and tissue damage. Subsequently, these changes result in organ failure and trigger a vicious cycle. In vitro and animal studies have identified an important role of mitochondrial dysfunction in heart failure (HF) and chronic kidney disease (CKD). Maintaining mitochondrial homeostasis may be a promising therapeutic strategy to interrupt the vicious cycle between HF and acute kidney injury (AKI)/CKD. In this review, we hypothesize that mitochondrial dysfunction may also play a central role in the development and progression of CRS. We first outline the pathophysiological mechanism of CRS and then focus on the role of mitochondrial dysfunction in the pathophysiology of HF and AKI/CKD. We also discuss the current research evidence supporting that mitochondrial dysfunction is involved in various types of CRS.